13x+7=12x-3

Simple and best practice solution for 13x+7=12x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13x+7=12x-3 equation:


Simplifying
13x + 7 = 12x + -3

Reorder the terms:
7 + 13x = 12x + -3

Reorder the terms:
7 + 13x = -3 + 12x

Solving
7 + 13x = -3 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
7 + 13x + -12x = -3 + 12x + -12x

Combine like terms: 13x + -12x = 1x
7 + 1x = -3 + 12x + -12x

Combine like terms: 12x + -12x = 0
7 + 1x = -3 + 0
7 + 1x = -3

Add '-7' to each side of the equation.
7 + -7 + 1x = -3 + -7

Combine like terms: 7 + -7 = 0
0 + 1x = -3 + -7
1x = -3 + -7

Combine like terms: -3 + -7 = -10
1x = -10

Divide each side by '1'.
x = -10

Simplifying
x = -10

See similar equations:

| -m+2=0 | | 3u^9*2x^4u^4*5x= | | -29/41-(-12/41) | | 6x^2-13=281 | | 1-3v=-20 | | 15n^2+17n+6=0 | | 6x-13=281 | | 1+4b=5 | | 1x/4-1=1x/7+2 | | 5+4m=29 | | 2-2p=6 | | 1.7=fraction | | -9=-14+b | | 0.285x^2-2x+2=0 | | 16=18+z | | x/2+17=22 | | 2p+5=25 | | -17=-15+x | | f(x)=895+30g | | 15n^2+17n=4 | | -2=-20+y | | -5b+4=39 | | 12+m=-8 | | B/3+6=24 | | -3n+4=19 | | 19=-8+n | | 6+5f+11r-7+3f+5(x+3)= | | -6(3x+9)+7= | | 25p+6p^2=-4 | | x^4+4x^3+(-8x^2)+2=0 | | x^2-4x+13=29 | | -3-5x=-18 |

Equations solver categories